Biocompatibility and Biodegradation of Deproteinized Human Demineralized Tooth Matrix (dpDTM) in Rabbit Model - Sureerat Tanwatana (Prince of Songkla University, 2021)
Thesis (M.Sc., Oral and Maxillofacial Surgery)--Prince of Songkla University, 2019